The neuroscience of empathy, compassion, and self-compassion - Stevens, Larry (Larry Charles); Woodruff, C. Chad (Christopher Chad) (Academic Press, an imprint of Elsevier, 2018)
The Neuroscience of Empathy, Compassion, and Self-Compassion provides contemporary perspectives on the three related domains of empathy, compassion and self-compassion (ECS). It informs current research, stimulates further research endeavors, and encourages continued and creative philosophical and scientific inquiry into the critical societal constructs of ECS. Examining the growing number of electrocortical (EEG Power Spectral, Coherence, Evoked Potential, etc.) studies and the sizeable body of exciting neuroendocrine research (e.g., oxytocin, dopamine, etc.) that have accumulated over decades, this reference is a unique and comprehensive approach to empathy, compassion and self-compassion. Provides perspectives on empathy, compassion and self-compassion (ECS), including discussions of cruelty, torture, killings, homicides, suicides, terrorism and other examples of empathy/compassion erosion Addresses autonomic nervous system (vagal) reflections of ECS Discusses recent findings and understanding of ECS from mirror neuron research Covers neuroendocrine manifestations of ECS and self-compassion and the neuroendocrine enhancement Examines the neuroscience research on the enhancement of ECS Includes directed-meditations (mindfulness, mantra, Metta, etc.) and their effects on ECS and the brain